METODE KAJIAN KITAB TAFSIR AL-IKLIL FI MA’ANI AL-TANZIL DENGAN FENOMENA SOSIAL DI PONDOK PESANTREN TAHSINUL AKHLAQ WINONG GEMPOL CIREBON - Kusen Kusen (UIN Siber Syekh Nurjati Cirebon, 2017)
Interpretation is knowledge of understanding the Koran. The study of al-Ikli l Fi interpretations Ma’ani al-Tanzi l by the scholar Misbah Mustafa Bangil in the Tahsinul Akhlaq Winong Gempol Islamic boarding school in Cirebon has been done since the 60s. This study affects the social and religious activities of the surrounding community. This paper explains the method of study of the book of interpretation and the social influence of the community. The results of his research are the study of interpretation using the method of deductive reasoning and oral interpretation with nazam-nazam Java.